2013
DOI: 10.1103/physrevc.87.025804
|View full text |Cite
|
Sign up to set email alerts
|

Maximum mass of a hybrid star having a mixed-phase region based on constraints set by the pulsar PSR J1614-2230

Abstract: Recent observation of pulsar PSR J1614-2230 with mass about 2 solar masses poses a severe constraint on the equations of state (EOS) of matter describing stars under extreme conditions. Neutron stars (NS) can reach the mass limits set by PSR J1614-2230. But stars having hyperons or quark stars (QS) having boson condensates, with softer EOS can barely reach such limits and are ruled out. QS with pure strange matter also cannot have such high mass unless the effect of strong coupling constant or color supercondu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 45 publications
(52 reference statements)
1
25
0
Order By: Relevance
“…Masses of the order of ≤ 1.8M ⊙ were obtained in non-relativistic phenomenological models [13,14], while microscopic models based on hyperon-nucleon potentials, which include the repulsive three-body forces, predict low maximal masses for hypernuclear stars [15,16]. The avenues for reconciliation of the large pulsar mass and the hyperonization (and more generally strangeness) of dense matter have been explored recently in Refs [17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Masses of the order of ≤ 1.8M ⊙ were obtained in non-relativistic phenomenological models [13,14], while microscopic models based on hyperon-nucleon potentials, which include the repulsive three-body forces, predict low maximal masses for hypernuclear stars [15,16]. The avenues for reconciliation of the large pulsar mass and the hyperonization (and more generally strangeness) of dense matter have been explored recently in Refs [17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, Demorest et al first observed the massive neutron star PSR J1614-2230 [1], which was soon theoretically studied by many researchers with various methods [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The total energy density and pressure of the strange quark matter is given by (Mallick, 2013; Mohanta…”
Section: Magnetic Field In Quark Phasementioning
confidence: 99%